ON the Vmm(S;A, Z)

ON the Vmm(S;A, Z)

Novi Sad J. Math. 99 Vol. 34, No. 1, 2004, 99-106 ON THE vMm(s; a; z) FUNCTION Aleksandar Petojevi´c1 1 Abstract. In this paper we study the special cases fvMm(s; m+n; z)gn=2 1 and fvMm(s; a; n)gn=1, where vMm(s; a; z) is the function defined in [8]. Also, we give connections between vMm(s; a; z) function and figured num- bers, Stirling numbers of the first kind and Riemann Zeta function. AMS Mathematics Subject Classification (2000): 11B34 Key words and phrases: vMm(s; a; z) function, factorial function, Rie- mann Zeta function, figured number, Stirling number 1. Introduction In 1971, Kurepa (see [4, 5]) defined so-called the left factorial !n by: nX¡1 !0 = 0; !n = k!(n 2 N) k=0 and extended it to the complex half-plane Re (z) > 0 as Z +1 tz ¡ 1 !z = e¡t dt: 0 t ¡ 1 Such function can be also extended analytically to the whole complex plane by !z =!(z + 1) ¡ Γ(z + 1), where Γ(z) is the gamma function defined by Z +1 Γ(z) = tz¡1e¡t dt (Re (z) > 0): 0 Recently, Milovanovi´c[6] defined and studied a sequence of the factorial +1 functions fMm(z)gm=¡1 where M¡1(z) = Γ(z) and M0(z) = !z. Namely, Z +1 z+m t ¡ Qm(t; z) ¡t (1.1) Mm(z) = m+1 e dt (Re (z) > ¡(m + 1)); 0 (t ¡ 1) where the polynomials Qm(t; z), m = ¡1; 0; 1; 2;:::, are given by µ ¶ Xm m + z Q (t; z) = 0;Q (t; z) = (t ¡ 1)k: ¡1 m k k=0 1University of Novi Sad, Teacher Training Faculty, Podgoriˇcka 4, 25000 Sombor, Serbia and Montenegro, E-mail: [email protected] 100 A. Petojevi´c Since (1.2) Mm(z) = Mm(z + 1) ¡ Mm¡1(z + 1) (m 2 N0); similar to the gamma function, the functions z 7! Mm(z), for each m 2 N0, can be extended analytically to the whole complex plane, starting from the corresponding analytic extension of the gamma function. Suppose that we have analytic extensions for all functions z 7! Mº (z), º < m. Let the function z 7! Mm(z) be defined by (1.1) for z in the half-plane Re (z) > ¡(m + 1). Using successively (1.2), we define at first Mm(z) for z in the strip ¡(m + 2) < Re (z) < ¡(m + 1), then for z such that ¡(m + 3) < Re (z) < ¡(m + 2), etc. In this way we obtain the function Mm(z) in the whole complex plane. In [8] the generalization is given of Milovanovi´c’sfactorial function: Definition 1.1 For m = ¡1; 0; 1; 2; ::: and Re (z) > v ¡ m ¡ 2 the function vMm(s; a; z) defined by µ ¶ Xv z + m + 1 ¡ k M (s; a; z) = (¡1)k¡1 L[s; F (a; k ¡ z; m + 2; 1 ¡ t)]; v m m + 1 2 1 k=1 where v is a positive integer, s; a; z are complex variables. The hypergeometric function 2F1(a; b; c; x) is defined by the series X1 (a) (b) xn F (a; b; c; x) = n n (jxj < 1); 2 1 (c) n! n=0 n and has the integral representation Z 1 Γ(c) b¡1 c¡b¡1 ¡a 2F1(a; b; c; x) = t (1 ¡ t) (1 ¡ tx) dt; Γ(b)Γ(c ¡ b) 0 in the x plane cut along the real axis from 1 to 1, if Re (c) > Re (b) > 0. The symbols (z)n and L[s; F (t)] represent the Pochhammer symbol Γ(z + n) (z) = 1; (z) = z(z + 1):::(z + n ¡ 1) = ; 0 n Γ(z) and Laplace transform Z 1 L[s; F (t)] = e¡stF (t)dt: 0 The binomial coefficient function defined via µ ¶ z Γ(z + 1) = : m Γ(m + 1)Γ(z ¡ m + 1) These function are of interest because their special cases include: On the vMm(s; a; z) function 101 1Mm(1; 1; z) = Mm(z) 1M¡1(1; 1; z) = Γ(z) 1M0(1; 1; z) = !z nM¡1(1; 1; n + 1) = An; where An denotes the alternating factorial numbers Xn n¡k An = (¡1) k!: k=1 For the complex half-plane Re (z) > 0; the function Az is defined by (see [8]) Z 1 z+1 z def x ¡ (¡1) x ¡x Az = e dx: 0 x + 1 However, apart from n!; !n and An twenty-five more well-known integer se- quences in [10] are special cases of the function vMm(s; a; z): 2. The statement results and proofs Investigation of the function vMm(s; a; z) by using the two statements could be translated to the investigation of the function 1Mm(s; a; z) as follows: apply- ing the relation 2Mm(s; a; z) = 1Mm(s; a; z) ¡ 1Mm(s; a; z ¡ 1); induction on v we have Xv k¡1 (2.3) vMm(s; a; z) = (¡1) 1Mm(s; a; z ¡ k + 1): k=1 Using the relation 2F1(a; 1 ¡ z; m + 2; 1 ¡ t) =2 F1(1 ¡ z; a; m + 2; 1 ¡ t)(j1 ¡ tj < 1) we have µ ¶ µ ¶ a + m z + m M (s; a; z) = M (s; 1 ¡ z; a): m + 1 1 m m + 1 1 m Hence (z)m+1 1Mm(s; a; z) = 1Mm(s; 1 ¡ z; a): (a)m+1 The relation (2.3) yields Xv Xv k¡1 k¡1 (z ¡ k + 1)m+1 (¡1) 1Mm(s; a; z ¡ k + 1) = (¡1) 1Mm(s; k ¡ z; a) (a)m+1 k=1 k=1 i.e., Xv k¡1 (z ¡ k + 1)m+1 (2.4) vMm(s; a; z) = (¡1) 1Mm(s; k ¡ z; a) : (a)m+1 k=1 102 A. Petojevi´c 1 2.1 The special case fvMm(s; m + n; z)gn=2 For the function vMm(s; a; z); the following special cases hold (see [8]): µ ¶µ ¶ n! z(z + 1):::(z + m) X1 n + m + 1 z ¡ 1 M (1; ¡n; z) = (¡1)kD ; 1 m (n + m + 1)! k + m + 1 k k k=0 nzΓ(z + m + 1) M (1=n; m + 2; z) = ; 1 m (m + 1)! where Dk denotes the derangement numbers (sequence A000166 in [10]). We now introduce a generalization of the last relation: Theorem 2.1. For every natural number n > 1 and Re (s) > 0; Re (z) > 0 we have vMm(s; m + n; z) = µ ¶ Xv (¡1)k¡1sk¡z¡1 nX¡2 n ¡ 2 = (¡s)iΓ(z + m + n ¡ k ¡ i) : (m + n ¡ 1)! i k=1 i=0 d Proof . Let the function ¯i (m; n) be defined by ( 0; if i + d · n ¡ 2; d ¯i (m; n) = m + n ¡ 1; if i + d > n ¡ 2: Since X1 (m + n) (1 ¡ z) (1 ¡ t)j F (m + n; 1 ¡ z; m + 2; 1 ¡ t) = j j (j1 ¡ tj < 1) 2 1 (m + 2) j! j=0 j using relations (see [1]) a(1 ¡ z) 2F1(a + 1; b; c; z) = (2a ¡ c ¡ az + bz) 2F1(a; b; c; z) + + (c ¡ a) 2F1(a ¡ 1; b; c; z) and (¡1)nΓ(z) (1 ¡ z) = n Γ(z ¡ n) we have 2F1(m + n; 1 ¡ z; m + 2; 1 ¡ t) = µ ¶ tz¡n+1(m + 1)! nX¡2 n ¡ 2 nY¡2 = (¡1)n¡iti (z ¡ d + ¯d(m; n)): (m + n ¡ 1)! i i i=0 d=1 On the vMm(s; a; z) function 103 Hence L[s; 2F1(m + n; 1 ¡ z; m + 2; 1 ¡ t)] = Z µ ¶ 1 tz¡n+1(m + 1)! nX¡2 n ¡ 2 = e¡st (¡1)n¡iti (m + n ¡ 1)! i 0 i=0 nY¡2 d £ (z ¡ d + ¯i (m; n)) dt d=1 µ ¶ (m + 1)! nX¡2 n ¡ 2 nY¡2 = (¡1)n¡i (z ¡ d + ¯d(m; n)) (m + n ¡ 1)! i i i=0 d=1 Z 1 £ e¡sttz¡n+1+i dt : 0 Since, for Re (s) > 0 and Re (z) > 0 Z 1 e¡sttz¡n+1+i dt = sn¡z¡i¡2 Γ(z ¡ n + i + 2) 0 we have L[s; 2F1(m + n; 1 ¡ z; m + 2; 1 ¡ t)] = µ ¶ (m + 1)! nX¡2 n ¡ 2 = (¡1)n¡isn¡z¡i¡2 Γ(z ¡ n + i + 2) (m + n ¡ 1)! i i=0 nY¡2 d £ (z ¡ d + ¯i (m; n)) d=1 µ ¶ (m + 1)! Γ(z) nX¡2 n ¡ 2 Γ(z + m + n ¡ 1 ¡ i) = (¡s)i ; (m + n ¡ 1)! sz i Γ(z + m + 1) i=0 so that 1Mm(s; m + n; z) = µ ¶ µ ¶ z + m (m + 1)! Γ(z) nX¡2 n ¡ 2 Γ(z + m + n ¡ 1 ¡ i) = (¡s)i m + 1 (m + n ¡ 1)! sz i Γ(z + m + 1) i=0 µ ¶ s¡z nX¡2 n ¡ 2 = (¡s)iΓ(z + m + n ¡ 1 ¡ i): (m + n ¡ 1)! i i=0 104 A. Petojevi´c The relation (2.3) yields vMm(s; m + n; z) = µ ¶ Xv (¡1)k¡1sk¡z¡1 nX¡2 n ¡ 2 = (¡s)iΓ(z + m + n ¡ k ¡ i) : (m + n ¡ 1)! i k=1 i=0 1 2.2 The special case fvMm(s; a; n)gn=1 1 The function fvMm(s; a; n)gn=1 can be expressed in terms of the falling factorial polynomials Γ(x + 1) [x] = 1; [x] = x(x ¡ 1):::(x ¡ n + 1) = (n 2 N) 0 n Γ(x ¡ n + 1) in the form Theorem 2.2.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    8 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us